SEPARATION OF GLUCOSE, FRUCTOSE AND MALTOSE MIXTURE USING HPLC EQUIPPED WITH AMINE-MODIFIED SILICA COLUMN - Muliamartana, Charissa
Various types of sugar contained in food and each type of sugar have different metabolic pathways in the body. One of the most effective methods of sugar analysis is High Performance Liquid Chromatography (HPLC). The use of amine-modified silica columns showed better separation results than silica columns alone. Amine-modified silica columns that are sold in the market are quite expensive, which encourages the manufacture of columns independently. In this study, amine-modified silica column particles have been synthesized with 4 different compounds, namely Tetraethyl orthosilicate (TEOS)-N-(3- Trimethoxysilylpropyl)diethylenetriamine (NTMSP), TEOS-3-Aminopropyl) trimethoxysilane (APTMS), Bis(3-(triethoxysilyl)propyl)amine (Bis-APTES) and Trimethoxy(3,3,3-trifluoropropyl)silane (TMTFPS). The results of the physically modified silica showed a change, namely the modified silica was not as sticky as the unmodified silica. However, from the FTIR results, no peaks were found in the 2900 cm-1 area even though there should have been a peak due to the C-H strain from CH2 of NTMSP and APTMS, so it can be concluded that the silica has been modified but only a small part has been modified. SEM results from NTMSP silica obtained a particle size of 542-839 nm and APTMS silica obtained a particle size of 423-791 nm. This measure can be used for HPLC with the consequence that the pressure required is high. Column test for sugar separation was carried out with HPLC with a flow rate of 1 ml / minute, RID detector and the volume injected was 20 µL. The results of the NTMSP column, APTMS column, Bis-APTES column, and TMTFPS column tests for water, glucose, fructose and maltose samples came out at the same time which showed no separation. For comparison, in this study also tested the commercial amine silica column obtained good separation results for the separation of glucose, fructose and maltose with a resolution of 2,12 for the peaks of fructose and glucose and 6,73 for peaks of glucose and maltose.